Poe's pervasive influence - Cantalupo, Barbara (Perspectives on Edgar Allan Poe., 2012)
Complementing and extending a project begun by Lois Vines' Poe Abroad (University of Iowa Press, 1999), Poe's Pervasive Influence includes essays on Poe's influence abroad from Japanese author, Edogawa Rampo, to Russian author, Nikolai Gogol, and takes a wider perspective on Poe's influence by including essays on Poe's impact on American authors from Harriet Jacobs to Joyce Carol Oates.